Efektifitas Pendayagunaan Dana Infaq Sedekah Produktif Dompet Dhuafa dalam Pemberdayaan Program MaggotIn - Fathimah Az-Zahroo; Subandi Subandi; Finny Ligery; Agus Setiawan (Bulletin of Indonesian Islamic Studies, 2024)
This study aimed to analyze the receipt and disbursement of charity and infaq funds, the implementation of economic empowerment, as well as the effectiveness of the utilization of productive charity and infaq funds in the MaggotIn program by the Dhuafa Wallet in Karang Anyar Village, South Lampung District. The object of this study involved 32 people, including the branch leadership of the Dhuafa Lampung Wallet, program managers, chairpersons and members of the beneficiary group. Research uses field qualitative descriptive method. Data collection was conducted through in-depth interviews, systematic observations, documentation review, and the administration of questionnaires for specific data points. The analysis of data employed an inductive descriptive-evaluative approach to derive meaningful insights. The results of the study indicate that; First, fundraising and Distribution of infaq and shataqah from donors to Lampung Dhuafa Wallet and CSR assistance PT Bukit Asam. Total funds of Rs 42,00,000 were spent on manufacturing of enclosures, land, seedlings, livestock feed material, training, operational, and other necessities in the MaggotIn programme. Second, program implementation includes feasibility studies, socialization, implementation, coaching, accompaniment, evaluation, and reporting. The program aims to manage organic waste and help reeconomize beneficiaries through maggot cultivation, catfish farming, and poultry. The program also conducts an Edu-Trip for organic waste management education. Third, the effectiveness of the MaggotIn Program was assessed as effective with an overall effectiveness indicator of 82.7%. The program succeeded in improving the welfare of the community from the beneficiaries’ economic perspective through the development of enterprises, such as fish and poultry farming, as well as maggot processing. The program also helped alleviate poverty in Karanyangar Village, South Lampung as well as demonstrated that productive infaq-charity impacts economic growth in underprivileged areas.